Evaluation of seven warm season grasses for beef production in the Campos Gerais, Paraná, Brazil - Postiglioni, Sérgio Roberto (Pesquisa Agropecuaria Brasileira, 2000)
With the objective to compare animal performance, carrying capacity and productivity in the period of three years seven warm season grasses were evaluated under continuous grazing, with crossbred Canchim steers, in the region of Campos Gerais, Paraná, Brazil. The grasses studied were Flórida limpograss, Roxinha limpograss, Kazungula setária, brachiaria Marandu, Nilegrass, Ipeamegrass and coastcross-1. Experimental design was in randomized blocks with two replications and the adoption of the put and take method. Nilegrass and Florida limpograss had the highest IVDMD and produced the highest daily gains per steer. Roxinha limpograss produced the greater forage yield and supported more animals per hectare. Florida limpograss, Nilegrass and Roxinha limpograss had the greatest liveweight gains per hectare, with similar beef production. Except for Roxinha limpograss and Ipeamegrass, all the grasses exhibited a marked decline in productivity during the evaluation.